Uji Kuat Tekan Beton Dengan Penambahan Limbah Ampas Kopi Sebagai Substitusi Parsial Semen - Arqowi Pribadi; Mega Ayundya Widiastuti (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Concrete is the main material used in construction and is a mixture of sand, gravel, cement and air. The addition of materials such as coffee grounds can be an environmentally friendly alternative to partially replace cement in concrete mixes. This study examines the effect of variations in the addition of coffee grounds on the compressive strength of concrete, with the proportions of coffee grounds tested being 0%, 2.5%, 5%, and 7.5%. Tests were conducted on concrete cylinders of 150 mm diameter and 300 mm height, and the compressive strength was measured after 28 days of treatment. The test results showed that the addition of coffee grounds caused a decrease in the compressive strength of the concrete, with the average compressive strength values at 0%, 2.5%, 5%, and 7.5% variations being 36.78 MPa, 20.94 MPa, 16.98 MPa, and 11.04 MPa, respectively. Although coffee grounds cannot completely replace cement, this material can potentially be used as an environmentally friendly alternative for non-structural concrete applications. It can reduce the waste of coffee grounds while reducing the use of cement in construction, albeit with an impact on concrete strength.